Diabetes and gut microbiome - Fliegerová, Kateřina Olša; Mahayri, Tiziana Maria; Sechovcová, Hana; Mekadim, Chahrazed; Mrázek, Jakub; Jarošíková, Radka; Dubský, Michal; Fejfarová, Vladimíra (Frontiers in Microbiology, 2025)
Diabetes mellitus represents a significant global health problem. The number of people suffering from this metabolic disease is constantly rising and although the incidence is heterogeneous depending on region, country, economic situation, lifestyle, diet and level of medical care, it is increasing worldwide, especially among youths and children, mainly due to lifestyle and environmental changes. The pathogenesis of the two most common subtypes of diabetes mellitus, type 1 (T1DM) and type 2 (T2DM), is substantially different, so each form is characterized by a different causation, etiology, pathophysiology, presentation, and treatment. Research in recent decades increasingly indicates the potential role of the gut microbiome in the initiation, development, and progression of this disease. Intestinal microbes and their fermentation products have an important impact on host metabolism, immune system, nutrient digestion and absorption, gut barrier integrity and protection against pathogens. This review summarizes the current evidence on the changes in gut microbial populations in both types of diabetes mellitus. Attention is focused on changes in the abundance of specific bacterial groups at different taxonomic levels in humans, and microbiome shift is also assessed in relation to geographic location, age, diet and antidiabetic drug. The causal relationship between gut bacteria and diabetes is still unclear, and future studies applying new methodological approaches to a broader range of microorganisms inhabiting the digestive tract are urgently needed. This would not only provide a better understanding of the role of the gut microbiome in this metabolic disease, but also the use of beneficial bacterial species in the form of probiotics for the treatment of diabetes.